Nanoquasicrystalline al-based matrix/γ-Al2O3 nanocomposites - Galano, Marina Lorena (2015)
Quasicrystalline aluminium alloys have been studied in the past years achieving higher strength than commercial Al alloys and retaining high strength at high temperature. In this work a quasicrystalline Al alloy matrix nanocomposite containing nanoceramic particles has been manufactured using ball milling and hot extrusion. For that purpose a nanoquasicrystalline Al–Fe–Cr–Ti alloy was manufactured by powder atomisation. Nanocomposites consisting of a quasicrystalline Al–Fe–Cr–Ti alloy matrix and reinforcement of γ-Al2O3 nano particles were manufactured. The effect of ball milling time on the microstructure and microhardness of the nanocomposite powders was investigated. Bulk materials were produced by consolidation and hot extrusion. The microstructure and microhardness of the extruded materials were characterised. The milling regime behaviour is discussed, and shows three different steps that have a significant effect on the rate of change of uniformity of the reinforcement distribution, matrix microstructure, powder size distribution and its microhardness. No significant decomposition of the quasicrystalline phase occurred over 30 h of milling. Strain increased and the crystallite size of the aluminium phase decreased with milling time, with the Al crystallite size reaching a steady state. Although the quasicrystalline phase decomposed during hot extrusion, the microhardness of the nanocomposite produced is significantly harder (227 ± 3 μHV500) than both the unreinforced quasicrystalline alloy (159 ± 1 μHV500) and crystalline aluminium nanocomposites reported in the literature [1]. Methods and analysis of material behaviour put forward in this work inform further understanding and optimisation of this and other nanocomposite systems containing a metastable microstructure matrix.